Cambio de paradigmas en América Latina : nuevos impulsos, nuevos temores - Mols, Manfred. (Asociación Alemana de Investigación sobre América Latina (ADLAF) : Fundación Friedrich Ebert : Editorial Nueva Sociedad, 1994)
"Multinational group of 18 contributors explore array of general and specific themes in Latin American foreign policy and international relations 'en un mundo cambiente.' Volume the result of 1993 conference of the sponsoring association and foundation"--Handbook of Latin American Studies, v. 57.